REFOS: A Renewable Energy Multi-Purpose Floating Offshore System - Dimitrios N. Konispoliatis; Georgios M. Katsaounis; Dimitrios I. Manolas; Takvor H. Soukissian; Stylianos Polyzos; Thomas P. Mazarakos; Spyros G. Voutsinas; Spyridon A. Mavrakos (Energies, 2021)
The present paper deals with the development of a multi-purpose floating tension leg platform (TLP) concept suitable for the combined offshore wind and wave energy resources exploitation, taking into account the prevailing environmental conditions at selected locations along the European coastline. The examined Renewable Energy Multi-Purpose Floating Offshore System (REFOS) platform encompasses an array of hydrodynamically interacting oscillating water column (OWC) devices, moored through tensioned tethers as a TLP platform supporting a 10 MW wind turbine (WT). The system consists of a triangular platform supported by cylindrical floaters, with the WT mounted at the deck’s center and the cylindrical OWC devices at its corners. Details of the modelling of the system are discussed and hydro-aero-elastic coupling between the floater; the mooring system; and the WT is presented. The analysis incorporates the solutions of the diffraction; the motion- and the pressure-dependent radiation problems around the moored structure, along with the aerodynamics of the WT into an integrated design approach validated through extensive experimental hydrodynamic scaled-down model tests. The verified theoretical results attest to the importance of the WT loading and the OWC characteristics on the dynamics of the system.